Optimising daytime deliveries when inducing labour using prostaglandin vaginal inserts. (16th February 2016) - Miller, Hugh; Goetzl, Laura; Wing, Deborah A.; Powers, Barbara; Rugarn, Olof
Abstract: Objective : To determine induction start time(s) that would maximise daytime deliveries when using prostaglandin vaginal inserts. Methods : Women enrolled into the Phase III trial, EXPEDITE (clinical trial registration: NCT01127581), had labour induced with either a misoprostol or dinoprostone vaginal insert (MVI or DVI). A secondary analysis was conducted to determine the optimal start times for induction by identifying the 12-h period with the highest proportion of deliveries by parity and treatment. Results : Optimal start times for achieving daytime deliveries when using MVI appear to be 19:00 in nulliparae and 23:00 in multiparae. Applying these start times, the median time of onset of active labour would be approximately 08:30 for both parities and the median time of delivery would be the following day at approximately 16:30 for nulliparae and 12:00 (midday) for multiparae. Optimal start times when using DVI appear to be 07:00 for nulliparae and 23:00 for multiparae. Using these start times, the median time of onset of active labour would be the following day at approximately 04:00 and 11:50, and the median time of delivery would be approximately 13:40 and 16:10, respectively. Conclusions : When optimising daytime deliveries, different times to initiate induction of labour may be appropriate depending on parity and the type of retrievable prostaglandin vaginal insert used.